EFFECT OF IMPRESSİON MANAGEMENT STRATEGİES ON PUBLİC EMPLOYEE SOCİAL LOAFİNG (Third Sector Social Economic Review, 2022)
Social loafing behavior is seen as a major risk factor for the productivity of organizations. Impression management is similarly a behavior that can create major problems in terms of transparency, honesty and reliability in the workplace. If these two behaviors are seen together, it is likely that serious problems will arise in terms of the organization. The aim of this study is to investigate the effect of impression management strategies on social loafing behavior of public institution employees. In the hypotheses created, it is stated that impression management tactics may have an effect on social loafing behavior and these hypotheses are tested. The research hypothesis was formed and tested by using the literature-based scales. The participants included in the research consist of civil servants at different levels working in three different public institutions in Ankara. The total number of participants is 254. The data of 4 participants were excluded from the sample due to missing answers and inconsistencies. As a result of the research, it has been determined that impression management strategies and all its sub-dimensions have a statistically significant and positive effect on social loafing behavior at different levels. It is of great importance to prevent social loafing and impression management behaviors that can cause serious productivity problems for organizations. As a result of the findings obtained in the study, suggestions were presented on measures that will raise awareness about impression management strategies in organizations and prevent social loafing behavior.
Keywords: Impression management Social Loafing; Organizational Performance; Productivity: Motivation